Cultura de la innovación y su influencia en la competitividad en la industria del calzado del distrito el porvenir, Trujillo - Urcia Cruz, Manuel (2014)
There search aims to measure innovation of products and processes companies shoe manufacturers District El Porvenir, Trujillo-Peru to propose improvements in the competitiveness of the footwear industry. It has developed a diagnostic footwear industry to measure the innovation process developed by the micro enterprises. For which the relevant variables of the innovation system was determined and with them the Enterprise Technological Innovation Indicator footwear sector was established. The study sample consisted of 252 formal undertakings to which was applied a survey of owners or managers leading the organization and management of them. The results obtained indicate that technological deficiencies in production, administration, logistics, among others is the main problem facing the sector. By measuring the innovation process, the sector has a rating of 2,168 "Partially innovative companies", indicating that there have been individual innovation efforts to improve access to markets, improve the design of their products, improvet heir process technology between other, but also, the results indicate that the absence of intellectual property development, process certification processes and /or products, you can’t successfully face today's competitive world.